Development of a continuity clinic curriculum for the section of Ambulatory Pediatrics of the Philippine General Hospital - Go, Elynn L.
The continuity clinic program of the Philippine General Hospital was first developed in 1991. It was primarily designed to promote continuity of care for the patients and at the same time, to teach the pediatric residents the importance of longitudinal care. However, the lack of a standard curriculum was a frequently mentioned problem. Hence, the objective of this study is to design a prototype curriculum in continuity care for pediatric residents in the Philippine General Hospital. Research and development (R and D) study design with triangulation of methods was utilized. The study was conducted in three phases: 1. Research and information collection; 2. Planning; and 3. Developing primary form of the product. Surveys, focus group discussions, key informant interviews, questionnaires and Delphi technique were utilized to develop the curriculum namely: 1. Demonstrate adeptness in all aspects of child visits 2. Emphasize the importance of preventive health care 3. Recognize common illness and treat them accordingly 4. Recognize cases needing urgent or emergent care 5. Care for chronically ill children 6. Establish rapport with patients and their families and 7. Demonstrate adeptness in handling various health related issues encountered in private practice. A competency based, integrated and experiential learning continuity care clinic curriculum has been developed as a response. The curriculum has been developed as a response. The curriculum developed for the continuity clinic rotation reflected the longitudinal experience of the pediatric residents and accentuated experiential learning. Increasing proficiency for each year level is emphasized. It is expected that the designed curriculum will match the present learning context of the residents and ensure their achievement of standard competencies identified which are part of their Pediatric residency training.